Modified carbon fiber, carbon fiber-reinforced resin, and producing method of modified carbon fiber
By controlling the ratio of carbon atoms on the surface of the carbon fiber and the internal voids, a gentle acid treatment method is used to form an appropriate amount of oxygen and nitrogen functional group on the surface of the carbon fiber, solving the problems of carbon fiber damage and poor adhesion, and achieving a carbon fiber composite with high strength and excellent adhesion.
Patent Information
- Application Number
- JP2023121691
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-26
- Publication Date
- 2025-02-06
AI Technical Summary
In the prior art, carbon fiber surface treatment methods may cause damage to carbon fibers, and there is a risk of damage when the carbon fiber composite material is heated in an oxygen atmosphere, affecting its adhesion effect with the resin.
By controlling the carbon atom ratio between the surface and internal voids of the carbon fibers, it contains 55.5 to 68.0 atoms of functional groups of oxygen and nitrogen, the carbon fibers are treated in an acidic solution in a gentle method to form an appropriate amount of functional groups to improve adhesion.
Excellent adhesion and high strength between carbon fiber and resin are achieved, damage caused by high temperature treatment is avoided, and the performance of carbon fiber composite materials is improved.
Smart Images

Figure 2025018189000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a modified carbon fiber, a carbon fiber reinforced resin, and a method for producing the modified carbon fiber, and more particularly to a modified carbon fiber having excellent fiber strength and excellent adhesion to resin, a carbon fiber reinforced resin using the modified carbon fiber, and a method for producing the modified carbon fiber. [Background technology]
[0002] Patent Document 1 discloses a method for surface treatment of carbon fibers that can efficiently increase the anchor effect by increasing the uneven surface on the carbon fiber surface, which is effective in improving adhesion to the matrix resin, and mainly introduce oxygen-containing functional groups by removing unnecessary components while leaving only the oxygen-containing functional groups. This method for surface treatment of carbon fibers is a method for surface treatment of carbon fibers by electrolytic oxidation, in which (a) first, electrolytic oxidation treatment is performed under harsh conditions in which the carbon fibers are used as the anode and an electric charge of 50 c / g or more is passed in an electrolyte, and (b) next, the fibers are washed with water, dried, and then heat-treated in an oxygen-containing atmosphere.
[0003] Patent Document 2 discloses a method for recovering carbon fibers by a completely new method that has not been used in the past and that can easily recover carbon fibers from a carbon fiber composite material. This method for recovering carbon fibers includes anodizing a carbon fiber composite material and decomposing at least a part of the carbon fiber composite material into fibers. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 5-44155 [Patent Document 2] JP 2013-249386 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, in the surface treatment method of carbon fiber as described in Patent Document 1, it is necessary to heat treat the carbon fiber in an oxygen-containing atmosphere at about 200 to 300°C, which is problematic in that the carbon fiber may be damaged. Also, in the carbon fiber recovery method as described in Patent Document 2, when the carbon fiber composite material is carbon fiber reinforced resin, it is necessary to heat treat the carbon fiber reinforced resin in an oxygen-containing atmosphere prior to anodization, which is problematic in that the carbon fiber may be damaged.
[0006] The present invention has been made in consideration of the problems associated with such conventional techniques, and aims to provide a modified carbon fiber having excellent fiber strength and excellent adhesion to resin, a carbon fiber reinforced resin using the modified carbon fiber, and a method for producing the modified carbon fiber. [Means for solving the problem]
[0007] As a result of extensive research into achieving the above-mentioned object, the inventors have found that the above-mentioned object can be achieved by configuring the carbon fiber so that, when the total number of carbon atoms present on the surface of the carbon fiber and on the surfaces of internal voids in the carbon fiber is taken as 100 atomic %, the proportion of carbon atoms to which a specified functional group is bonded is within a specified range, and have thus completed the present invention.
[0008] In other words, in the modified carbon fiber of the present invention, when the sum of the carbon atoms present on the surface of the carbon fiber and on the surfaces of the internal voids of the carbon fiber is taken as 100 atomic %, the proportion of carbon atoms bonded to functional groups containing at least one of oxygen and nitrogen elements is 55.5 atomic % or more and 68.0 atomic % or less.
[0009] The carbon fiber reinforced resin of the present invention is a carbon fiber reinforced resin obtained by reinforcing a resin with modified carbon fiber. In the modified carbon fiber, when the sum of the carbon atoms present on the surface of the carbon fiber and on the surfaces of the internal voids of the carbon fiber is taken as 100 atomic %, the proportion of carbon atoms bonded to functional groups containing at least one of oxygen and nitrogen elements is 55.5 atomic % or more and 68.0 atomic % or less.
[0010] Furthermore, the method for producing modified carbon fibers of the present invention is a method for producing modified carbon fibers in which, when the sum of the carbon atoms present on the surface of the carbon fiber and on the surfaces of internal voids in the carbon fiber is taken as 100 atomic %, the proportion of carbon atoms bonded to functional groups containing at least one of oxygen and nitrogen elements is 55.5 atomic % or more and 68.0 atomic % or less. In the method for producing the modified carbon fiber, when producing the modified carbon fiber, a carbon fiber reinforced resin containing carbon fiber and a resin or a carbon fiber is immersed in an aqueous nitric acid solution having a temperature of 60°C or more and a concentration of 4 mol / L or more and 8 mol / L or less for 8 hours or more. Effect of the Invention
[0011] According to the present invention, when the sum of the carbon atoms present on the surface of the carbon fiber and on the surfaces of the internal voids of the carbon fiber is taken as 100 atomic %, the proportion of carbon atoms to which the above-mentioned functional groups are bonded is within the above-mentioned range, so that it is possible to provide a modified carbon fiber having excellent fiber strength and excellent adhesion to resin, a carbon fiber reinforced resin using the modified carbon fiber, and a method for producing the modified carbon fiber. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is an explanatory diagram showing a method for recovering recycled carbon fibers from carbon fiber reinforced plastic parts for automobiles using a nitric acid decomposition method. [Diagram 2] 1 shows a scanning electron microscope image and a photograph of virgin carbon fiber (Test Example 1), and a scanning electron microscope image and a photograph of carbon fiber (Test Example 2) recovered after immersing virgin carbon fiber in an aqueous nitric acid solution for 8 hours. [Diagram 3] Scanning electron microscope images and photographs of recycled carbon fiber (Test Example 3) recovered from a carbon fiber reinforced resin sample for automobiles after immersion in an aqueous nitric acid solution for 8 hours, and scanning electron microscope images and photographs of recycled carbon fiber (Test Example 4) recovered from a carbon fiber reinforced resin sample for automobiles after immersion in an aqueous nitric acid solution for 12 hours. [Figure 4]Scanning electron microscope images and photographs of recycled carbon fiber (Test Example 5) recovered from a carbon fiber reinforced resin sample for automobiles after immersion in an aqueous nitric acid solution for 24 hours, and scanning electron microscope images and photographs of recycled carbon fiber (Test Example 6) recovered from a carbon fiber reinforced resin sample for automobiles after immersion in an aqueous nitric acid solution for 120 hours. [Diagram 5] 1 is a graph showing the results of the interfacial shear strength between the carbon fiber and the resin in each test example obtained by a microdroplet test. [Figure 6] 1 is a graph showing the results of the tensile strength of the carbon fibers of each test example obtained by a tensile strength test. [Figure 7] 1 shows transmission electron microscope images of the cross sections of carbon fibers having a thickness of about 100 nm in Test Example 1 and Test Example 2 produced by focused ion beam processing. [Figure 8] 13A and 13B are transmission electron microscope images of cross sections of carbon fibers having a thickness of about 100 nm in Test Examples 4 and 5 produced by focused ion beam processing. [Figure 9] 1 is a transmission electron microscope image of a cross section of a carbon fiber having a thickness of about 100 nm in Test Example 6 produced by focused ion beam processing. [Figure 10] FIG. 2 is a diagram showing the results of element mapping (target elements: C, N, O) by energy dispersive X-ray analysis on the cross section of the carbon fiber of Test Example 1 produced by focused ion beam processing. [Figure 11] FIG. 1 shows the results of element mapping (target elements: C, N, O) by energy dispersive X-ray analysis on the cross section of the carbon fiber of Test Example 2 produced by focused ion beam processing. [Figure 12] FIG. 1 shows the results of element mapping (target elements: C, N, O) by energy dispersive X-ray analysis on the cross section of the carbon fiber of Test Example 4 produced by focused ion beam processing. [Figure 13] FIG. 13 is a diagram showing the results of element mapping (target elements: C, N, O) by energy dispersive X-ray analysis on the cross section of the carbon fiber of Test Example 5 produced by focused ion beam processing. [Figure 14]FIG. 13 is a diagram showing the results of element mapping (target elements: C, N, O) by energy dispersive X-ray analysis on the cross section of the carbon fiber of Test Example 6 produced by focused ion beam processing. [Figure 15] 1 is a graph showing the peak area ratio of ID1 / IG1 calculated from the Raman spectrum obtained by Raman spectrometry. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, one embodiment of the modified carbon fiber, the carbon fiber reinforced plastic (CFRP) using the modified carbon fiber, and the method for producing the modified carbon fiber of the present invention will be described in detail.
[0014] <Modified carbon fiber> In the modified carbon fiber of this embodiment, when the sum of the carbon atoms present on the surface of the carbon fiber and on the surfaces of the internal voids of the carbon fiber is taken as 100 atomic %, the proportion of carbon atoms bonded to functional groups containing at least one of oxygen and nitrogen elements is 55.5 atomic % or more and 68.0 atomic % or less.
[0015] According to this embodiment, when the total number of carbon atoms present on the surface of the carbon fiber and on the surface of the internal voids of the carbon fiber is taken as 100 atomic %, the ratio of carbon atoms to which the above-mentioned functional groups are bonded is within the above-mentioned range, so that the above-mentioned functional groups capable of bonding with the matrix resin of CFRP can be present on the surface of the carbon fiber in an appropriate ratio. This makes it possible to obtain modified carbon fibers having superior fiber strength and superior adhesion to resin compared to virgin carbon fibers before they are impregnated with the resin used in CFRP parts.
[0016] In addition, according to the present embodiment, there is an advantage that the modified carbon fiber can be applied to applications requiring higher performance than applications requiring virgin carbon fiber manufactured with relatively low quality. Furthermore, according to the present embodiment, there is an advantage that the modified carbon fiber applicable to applications requiring higher performance can be obtained by recycling the carbon fiber reinforced resin.
[0017] When the total number of carbon atoms present on the surface of the carbon fiber and on the surface of the internal voids of the carbon fiber is taken as 100 atomic %, if the ratio of carbon atoms to which the functional groups are bonded is less than 55.5 atomic %, the number of functional groups involved in the adhesion to the resin is small, and the adhesion to the resin may not be improved. In addition, if the ratio of carbon atoms to which the functional groups are bonded is greater than 68.0 atomic %, the effect of improving the adhesion to the resin becomes saturated. From the viewpoint of further improving the adhesion, it is more preferable that the ratio of carbon atoms to which the functional groups are bonded is 63.0 atomic % or more and 68.0 atomic % or less.
[0018] Suitable examples of the functional groups include carboxy, carbonyl, formyl, alkoxy, ester, amino, nitro, nitroso, ammonio, cyano, sulfo, and hydroxyl groups, and these may be used alone or in combination of two or more. Here, functional groups such as carboxy, carbonyl, formyl, alkoxy, ester, amino, nitro, nitroso, ammonio, cyano, and hydroxyl groups can be formed, for example, by immersing the carbon fiber reinforced resin in an aqueous nitric acid solution. The sulfo group can be formed, for example, by immersing the carbon fiber reinforced resin in an aqueous nitric acid solution to which sulfuric acid has been added.
[0019] The modified carbon fiber preferably has voids inside the carbon fiber, and the functional groups described above are present in the voids. The presence of the functional groups in the voids can reduce the number of stress concentration origins when a tensile load is applied to the carbon fiber, and the tensile strength of the modified carbon fiber can be further improved compared to that of virgin carbon fiber.
[0020] The modified carbon fiber preferably has voids at a ratio of 0.1 area % or more and 3.2 area % or less per unit cross-sectional area of the carbon fiber. When the modified carbon fiber has voids at the above ratio, it indicates that the graphite structure constituting the carbon fiber is hardly damaged and the fragile graphite layer present on the surface of the carbon fiber has been removed. This makes it possible to reduce the number of origins of stress concentration when a tensile load is applied to the modified carbon fiber, and the tensile strength of the modified carbon fiber can be further improved compared to the tensile strength of virgin carbon fiber having voids at a ratio of more than 3.2 area %. From the viewpoint of further improving the above-mentioned fiber strength, it is more preferable that the modified carbon fiber has voids at a ratio of 1.0 area % or more and 1.1 area % or less per unit cross-sectional area of the carbon fiber.
[0021] Furthermore, in the modified carbon fiber, the intensity ratio of the D1 band of the carbon fiber to the G1 band of the carbon fiber obtained by Raman spectroscopy (I D1 / I G1 ) is preferably 3.4 or less, and more preferably 2.1 or more. When it is within the above-mentioned numerical range, almost no damage occurs to the crystal structure of the graphite structure of the carbon fiber, so that the tensile strength of the modified carbon fiber can be further improved compared to the tensile strength of virgin carbon fiber. From the viewpoint of further improving the above-mentioned fiber strength and adhesion, the above-mentioned strength ratio (I D1 / I G1 ) is more preferably 2.1 or more and 2.3 or less.
[0022] <Carbon fiber reinforced resin> The carbon fiber reinforced resin of this embodiment is a carbon fiber reinforced resin obtained by reinforcing a resin with modified carbon fiber. In the modified carbon fiber, when the total number of carbon atoms present on the surface of the carbon fiber and on the surface of the internal void of the carbon fiber is taken as 100 atomic %, the ratio of carbon atoms bonded to functional groups containing at least one element selected from oxygen and nitrogen elements is 55.5 atomic % or more and 68.0 atomic % or less.
[0023] According to this embodiment, modified carbon fibers are used in which the proportion of carbon atoms to which the above-mentioned functional groups are bonded falls within the above-mentioned range when the sum of the carbon atoms present on the surface of the carbon fiber and on the surface of the internal voids of the carbon fiber is taken as 100 atomic %, so that a CFRP having better physical properties than a CFRP made from virgin carbon fiber before it is impregnated with the resin used in CFRP parts can be obtained.
[0024] <Method of manufacturing modified carbon fiber> The method for producing the modified carbon fiber of this embodiment is a method for producing a modified carbon fiber in which the ratio of carbon atoms to which functional groups containing at least one element selected from oxygen and nitrogen are bonded is 55.5 atomic % or more and 68.0 atomic % or less, when all elements present on the surface of the carbon fiber and on the surface of the internal voids of the carbon fiber are taken as 100 atomic %. In the method for producing the modified carbon fiber of this embodiment, the carbon fiber reinforced resin or carbon fiber containing the carbon fiber and the resin is immersed in a nitric acid aqueous solution having a temperature of 60° C. or more and 80° C. or less and a concentration of 4 mol / L or more and 8 mol / L or less for 8 hours or more. In addition, when the carbon fiber reinforced resin is immersed in the nitric acid aqueous solution, the immersion time is preferably 24 hours or less, more preferably 10 hours or more and 18 hours or less.
[0025] According to this embodiment, modified carbon fibers having superior fiber strength and superior adhesion to resin to virgin carbon fibers before being impregnated with resin used in CFRP parts can be obtained with a good yield under relatively mild and simple treatment conditions compared to the treatments described in the above-mentioned Patent Documents 1 and 2. In addition, according to this embodiment, there is an advantage that the decomposed resin components can be recovered in a state dissolved in the nitric acid aqueous solution.
[0026] When the temperature of the aqueous nitric acid solution is less than 60°C, or the concentration is less than 4 mol / L, there are few functional groups involved in the adhesion to the resin, and the adhesion to the resin may not be improved. Furthermore, when the immersion time in the aqueous nitric acid solution is less than 8 hours, there is also a possibility that the functional groups involved in the adhesion to the resin may not be improved. Furthermore, when the temperature of the aqueous nitric acid solution is more than 80°C, the aqueous nitric acid solution boils and evaporates, so that the carbon fiber reinforced resin containing the carbon fiber and the resin may not be immersed in the aqueous nitric acid solution for 8 hours or more. Furthermore, when the concentration of the aqueous nitric acid solution is more than 8 mol / L, or when the immersion time in the aqueous nitric acid solution is more than 24 hours, the crystal structure of the graphite structure of the carbon fiber is damaged. From the viewpoint of obtaining modified carbon fiber having excellent fiber strength and excellent adhesion to the resin with a higher yield, it is preferable to set the immersion time to 10 hours or more and 18 hours or less. EXAMPLES
[0027] The present invention will be described in more detail below with reference to some test examples, but the present invention is not limited to these test examples.
[0028] (A) Sample preparation As shown in Fig. 1, waste automotive CFRP parts impregnated with epoxy resin were crushed to prepare CFRP samples.
[0029] (B) Method for recovering recycled carbon fibers using aqueous nitric acid solution In addition, the CFRP sample was immersed in an aqueous solution of nitric acid adjusted to 8 mol / L for a certain period of time in an 80°C environment, and then recycled carbon fiber (hereinafter referred to as "rCF") was obtained.
[0030] (C) Treatment of virgin carbon fiber with aqueous nitric acid solution Virgin carbon fiber (hereinafter referred to as "vCF") before being impregnated with resin, which was used in CFRP parts for automobiles, was immersed in an aqueous nitric acid solution adjusted to 8 mol / L for a certain period of time in an 80°C environment to obtain vCF immersed in an aqueous nitric acid solution.
[0031] (D) Surface observation of vCF and rCF As shown in Figures 2 to 4, in the case of vCF recovered after immersion in a nitric acid aqueous solution for 8 hours (hereafter referred to as "vCF8h"; the same applies below), no damage to the surface due to immersion in the nitric acid aqueous solution was observed, and a clean surface was confirmed that was no different from vCF. In the case of rCF recovered after immersion of a CFRP sample in a nitric acid aqueous solution for 8 hours (hereafter referred to as "rCF8h"; the same applies below), resin residue was confirmed on the surface because the immersion time was short and the resin was not fully decomposed. A small amount of resin residue was also confirmed locally on the surface of rCF12h, but the rCF (rCF24h, rCF120h) that were fully immersed in the nitric acid aqueous solution and then recovered had a clean surface without any resin residue.
[0032] (E) Microdroplet test (E-1) Evaluation Method The adhesion between the carbon fiber and the epoxy resin was evaluated by performing a microdroplet test on vCF and rCF. The single fiber pull-out speed in the microdroplet test was 0.12 mm / min, and the maximum load F (mN) when the resin droplet was pulled out was measured, and the interfacial shear strength τ (MPa) was calculated using equation (1).
[0033] τ=F / πdL×10 3 (1) Here, F is the maximum load measured (mN), d is the carbon fiber diameter (standard value d: 7.0 μm), and L is the diameter of the resin ball (measured value: 70 to 90 μm).
[0034] Since it has been reported that there is a positive correlation between the interfacial shear strength τ and the diameter L of the resin beads, the τ values obtained in the measurements were plotted against the diameter L of the resin beads used in the measurements, a linear regression equation was obtained, and the interfacial shear strength τ corresponding to a resin bead of 70 μm was calculated, thereby calculating the interfacial shear strength value for resin beads of the same size. The results are shown in Figure 5.
[0035] (E-2) Evaluation Results The interfacial shear strength τ of vCF was 30±3.1MPa, whereas rCF12h and rCF24h showed significantly higher values, and it was confirmed that the values were 2.2 times higher than that of vCF.
[0036] (F) Quantification of the amount of functional groups on the carbon fiber surface by X-ray photoelectron spectroscopy Normally, the surface of carbon fiber is inactive, so it cannot form a bond with the matrix resin as it is. Therefore, surface treatment is performed to impart polar functional groups to the surface of virgin carbon fiber for bonding with resin. From the results shown in E-2 above, it is presumed that the bonding strength with resin was improved because functional groups derived from nitric acid were imparted to the surface of carbon fiber during the process of decomposing the epoxy resin with nitric acid aqueous solution. Therefore, elemental analysis was performed using X-ray photoelectron spectroscopy on the surface of carbon fiber of each test example, and the composition ratio of functional groups contained in the carbon fiber of each test example is summarized in Table 1. In addition, the total presence ratio of functional groups involved in bonding with resin (C-OH, COC, >C=O, -CO-O-, -NH2, -NO / NH4, -NO2, O) among these functional groups is shown in the bottom row of Table 1.
[0037] [Table 1]
[0038] In Table 1, it was confirmed that functional groups involved in bonding with the resin were present at 52.2 atomic % in vCF, and the amount of functional groups present increased in vCF8h, rCF12h, rCF24h, and rCF120h. A correlation was observed between the amount of functional groups involved in bonding with the resin and the value of the interfacial shear strength with the resin shown in Figure 5, which indicates that functional groups derived from nitric acid were added to the surface of the carbon fiber during the process of decomposing the epoxy resin with an aqueous nitric acid solution.
[0039] (G) Carbon fiber tensile test (G-1) Evaluation Method Tensile tests for vCF and rCF single fibers were performed based on JIS R 7606. Both ends of the carbon fiber were pulled at a tensile speed of 1 mm / min, and the maximum load F' (mN) measured by the testing machine when the single fiber broke was recorded, and the tensile strength σ (GPa) was calculated using equation (2).
[0040] σ=4F' / πd 2 (2) Here, F' is the maximum load (mN) measured when a single fiber breaks, and d is the carbon fiber diameter (standard value d: 7.0 μm).
[0041] (G-2) Evaluation Results As shown in Figure 6, the tensile strength of vCF was σ = 0.75 ± 0.007 GPa, while that of rCF24h was σ = 1.02 ± 0.019 GPa. Here, the variation in tensile strength values was calculated as the standard deviation value when approximating the Weibull distribution. Similar to the phenomenon observed in the interfacial shear strength with the resin, it was confirmed that the tensile strength of the single fiber of the recycled carbon fibers (rCF12h and rCF24h) recovered after sufficient immersion in a nitric acid aqueous solution was improved to 1.4 times that of vCF.
[0042] (H) Observation of carbon fiber cross section (H-1) Evaluation Method To observe the cross section of the carbon fiber, a cross section with a thickness of about 100 nm was prepared using focused ion beam processing. The prepared cross section was observed using a transmission electron microscope, and the element distribution in the cross section was observed using an energy dispersive X-ray spectrometer.
[0043] (H-2) Evaluation Results As shown in Figures 7 to 9, the results of observation of vCF using a transmission electron microscope confirmed that voids were present in the region 400 nm inside from the carbon fiber surface, and their size was approximately 1 to 30 nm. Furthermore, the results of observation of vCF8h, rCF12h, rCF24h, and rCF120h using a transmission electron microscope showed that the void ratio was lower than that of vCF, and the void presence region was also 50 nm inside from the surface, which was the extreme surface layer compared to vCF. Here, the void ratio in any cross section of the observed carbon fiber was quantified using ImageJ image analysis software, and the results are shown in Table 2.
[0044] [Table 2]
[0045] Table 2 shows that the void ratio in vCF8h, rCF12h, rCF24h, and rCF120h is reduced to about 1 / 3 of that in vCF. This is thought to be because the graphite structure itself in the surface layer is removed by nitric acid.
[0046] Furthermore, element mapping was performed on the observed void parts by energy dispersive X-ray spectroscopy using C, N, and O as target elements. The results are shown in Figures 10 to 14. As can be seen from Figures 10 to 14, not only C element but also N element and O element were not confirmed in the void parts of vCF. On the other hand, like vCF, C element was not confirmed in the void parts of vCF8h, rCF12h, rCF24h, and rCF120h, but it was confirmed that O element and N element were present in high concentrations in the void parts.
[0047] From the above results, the following two factors can be considered as reasons why the tensile strength of recycled carbon fiber is improved compared to virgin carbon fiber.
[0048] First, the ratio of voids decreased from vCF8h, rCF12h, and rCF24h to rCF120h. Carbon fiber is a brittle material, and its strength is known to be greatly affected by defects on the surface and inside of the carbon fiber. It is also known that the smaller the void diameter inside the carbon fiber, the higher the fiber strength. Therefore, in fibers with improved tensile strength, the number of stress concentration points when a tensile load is applied is reduced due to the decrease in the ratio of voids, which is thought to have improved the tensile strength.
[0049] Secondly, it is believed that the incorporation of functional groups containing at least one of oxygen and nitrogen elements into the voids reduces the number of points of stress concentration when a tensile load is applied to the carbon fiber, thereby improving the tensile strength compared to untreated virgin carbon fiber.
[0050] (I) Evaluation of the graphite structure of carbon fibers (I-1) Evaluation method Raman spectroscopy was performed, and the areas of the G1 and D1 peaks in the obtained Raman spectrum were calculated. The G1 peak represents a peak derived from a six-membered carbon ring structure (high crystallinity), while the D1 peak represents a peak derived from structural disorder (low crystallinity) such as partial cleavage of the six-membered carbon ring. Therefore, the graphite structure was evaluated by taking the peak area ratio of D1 / G1. The results are shown in Figure 15.
[0051] (I-2) Evaluation results As shown in Figure 15, there was no significant change in rCF12h and rCF24h compared to vCF. On the other hand, vCF8h showed a value 1.3 times higher than vCF, and rCF120h showed a value 1.7 times higher than vCF. These results indicate that the graphite structure on the surface of rCF120h was disturbed and the crystallinity was reduced. Here, from the results in Figure 6, it was observed that the tensile strength of rCF120h decreased, but this is thought to be due to damage such as graphite structure disturbance and loss caused by immersing the carbon fiber in the nitric acid aqueous solution for a long time, as shown in this result.
[0052] 5 and 6 show that Test Examples 2 to 6, which are within the scope of the present invention, have excellent fiber strength and excellent adhesion to the resin. Also, from the viewpoints of fiber strength and adhesion, Test Examples 4 and 5, and especially Test Example 4, appear to provide the best results, as shown in Figs. 5, 6, and 15.
[0053] Although the present invention has been described above with reference to some embodiments and test examples, the present invention is not limited to these, and various modifications are possible within the scope of the gist of the present invention.
[0054] The present invention is based on the principle that the surface of the carbon fiber has the above-mentioned functional groups in the above-mentioned ratio in order to provide a modified carbon fiber having excellent fiber strength and excellent adhesion to resin, a carbon fiber reinforced resin using the modified carbon fiber, and a method for producing the modified carbon fiber.
[0055] Furthermore, for example, the above-mentioned components are not limited to the configurations shown in each embodiment or each test example, and it is possible to change the details of the specifications and materials of the virgin carbon fiber and resin, or to combine and apply the components of one embodiment with the components of another embodiment.
Claims
1. A modified carbon fiber, characterized in that, when the sum of the carbon atoms present on the surface of the carbon fiber and on the surfaces of internal voids of the carbon fiber is taken as 100 atomic %, the proportion of the carbon atoms bonded to functional groups containing at least one of oxygen and nitrogen elements is 55.5 atomic % or more and 68.0 atomic % or less.
2. 2. The modified carbon fiber according to claim 1, characterized in that the functional group contains at least one selected from the group consisting of a carboxy group, a carbonyl group, a formyl group, an alkoxy group, an ester group, an amino group, a nitro group, a nitroso group, an ammonio group, a cyano group, a sulfo group and a hydroxyl group.
3. 2. The modified carbon fiber according to claim 1, characterized in that the carbon fiber has voids therein, the voids being present in an amount of 0.1 area % or more and 3.2 area % or less per unit cross-sectional area of the carbon fiber.
4. 4. The modified carbon fiber of claim 3, wherein functional groups containing at least one of the oxygen and nitrogen elements are present within the voids.
5. The intensity ratio of the D1 band of the carbon fiber to the G1 band of the carbon fiber obtained by Raman spectroscopy (I D1 / I G1 5. The modified carbon fiber according to claim 3, wherein the tensile strength (T) of the modified carbon fiber is 3.4 or less.
6. A carbon fiber reinforced resin obtained by reinforcing a resin with modified carbon fiber, In the modified carbon fiber, when the total number of carbon atoms present on the surface of the carbon fiber and on the surface of the internal voids of the carbon fiber is taken as 100 atomic %, the ratio of the carbon atoms to which a functional group containing at least one element selected from oxygen and nitrogen is bonded is 55.5 atomic % or more and 68.0 atomic % or less. A carbon fiber reinforced resin.
7. When the sum of the carbon atoms present on the surface of the carbon fiber and on the surface of an internal void of the carbon fiber is taken as 100 atomic %, the ratio of the carbon atoms to which a functional group containing at least one element selected from oxygen and nitrogen is bonded is 55.5 atomic % or more and 68.0 atomic % or less, Carbon fiber reinforced resin containing carbon fiber and resin or carbon fiber is immersed in an aqueous nitric acid solution having a temperature of 60° C. to 80° C. and a concentration of 4 mol / L to 8 mol / L for 8 hours or more. A method for producing modified carbon fiber.
Citation Information
Patent Citations
Surface treatment of carbon fiber
JP1993044155A
Method for recovering carbon fiber from carbon fiber composite material
JP2013249386A